The relationship between intraoperative hypothermia and the ccurrence of surgical site infections: a meta-analysis of observational studies - Ju, Jing; Zhou, Feng; Wang, Zhenzhi (Frontiers in Surgery, 2024)
Objective: Inconsistent evidence exists regarding the association between intraoperative hypothermia and incidence of surgical site infection (SSI). This study aimed to determine the association between intraoperative hypothermia and SSI.A systematic review was conducted using Embase, PubMed, and Web of Science to identify observational studies evaluating the risk of SSI in patients with intraoperative hypothermia. The primary outcome measure was the diagnosis of SSI within 30 days of surgery. The pooled risk ratio was estimated using a fixed-or random-effect meta-analysis. Sensitivity analyses were performed to examine the impact of the structural design of preoperative warming on the pooled risk of SSI.Results: Five studies representing 6002 patients were included in the present metaanalysis. Intraoperative hypothermia was not associated with SSI risk in patients (HR = 1.22, 95% CI: 0.95-2.24, P = 0.119). The pooled hazard ratio showed that intraoperative hypothermia did not result in a higher risk of SSI.Intraoperative hypothermia was not associated with the risk of SSI.Further studies using objective exposure measurements are required to confirm these results.